Ordering and order-disorder phase transition in the (1x1) monolayer chemisorbed on the (111) face of an fcc crystal - Patrykiejew, A.; Staszewski, T. (Condensed Matter Physics, 2016)
In this paper we have considered a simple lattice gas model of chemisorbed monolayer which allows for the harmonic fluctuations of the bond length between the adsorbate atom and the surface site. The model also involves a short-ranged attractive potential acting between the adsorbed atoms as well as the surface periodic corrugation potential. It has been assumed that the adsorbed atoms are bonded to the uppermost layer of the substrate atoms. In particular, using Monte Carlo simulation method we have focused on the orderings appearing in the dense monolayer formed on the (111) face of an fcc solid. Within the lattice gas limit, the chemisorbed layer forms a (1x1) structure. On the other hand, when the bonds are allowed to fluctuate, three other different ordered phases have been found to be stable in the ground state. One of them has been found to be stable at finite temperatures and to undergo a phase transition to the disordered state. The remaining two ordered states have been found to be stable in the ground state only. At finite temperatures, the ordering has been demonstrated to be destroyed due to large entropic effects. В цiй статтi ми розглянули просту модель граткового газу хемосорбованого моношару, яка дозволяє здiйснювати гармонiчнi флуктуацiї довжини зв’язку мiж атомами адсорбату та поверхнi. Дана модель мiстить
короткосяжний потенцiал притягання, який дiє мiж адсорбованими атомами, а також поверхневий перiодичний гофрований потенцiал. Зроблено припущення, що адсорбованi атоми є зв’язанi з найвищим
шаром атомiв пiдкладки. Зокрема, використовуючи метод моделювання Монте Карло, акцент зроблено
на впорядкуванi у щiльному моношарi, сформованому на (111) гранi fcc кристалу. В границi граткового
газу хемосорбований шар утворює (1 × 1) структуру. З iншого боку, коли наявнi флуктуацiї зв’язкiв, три
iншi впорядкованi фази є стiйкими в основному станi. Встановлено, що одна з них є стiйкою при скiнчених температурах i переходить у невпорядкований стан. Двi iншi впорядкованi фази є стiйкими лише в
основному станi. Показано, що при скiнчених температурах впорядкування руйнується завдяки сильним
ентропiйним ефектам.